Multiple Interactions of Rad23 Suggest a Mechanism for Ubiquitylated Substrate Delivery Important in Proteolysis - Kim, Ikjin (The American Society for Cell Biology, 2004)
The mechanism underlying the delivery of ubiquitylated substrates to the proteasome is poorly understood. Rad23 is a putative adaptor molecule for this process because it interacts with ubiquitin chains through its ubiquitin-associated motifs (UBA) and with the proteasome through a ubiquitin-like element (UBL). Here, we demonstrate that the UBL motif of Rad23 also binds Ufd2, an E4 enzyme essential for ubiquitin chain assembly onto its substrates. Mutations in the UBL of Rad23 alter its interactions with Ufd2 and the proteasome, and impair its function in the UFD proteolytic pathway. Furthermore, Ufd2 and the proteasome subunit Rpn1 compete for the binding of Rad23, suggesting that Rad23 forms separate complexes with them. Importantly, we also find that the ability of other UBL/UBA proteins to associate with Ufd2 correlates with their differential involvement in the UFD pathway, suggesting that UBL-mediated interactions may contribute to the substrate specificity of these adaptors. We propose that the UBL motif, a protein-protein interaction module, may be used to facilitate coupling between substrate ubiquitylation and delivery, and to ensure the orderly handoff of the substrate from the ubiquitylation machinery to the proteasome.